Manfaat Dukungan Emosional dan Koping Spiritual terhadap Distress Psikologis pada Pelaku Rawat Orang Dengan Skizofrenia - Muri Cahyono Purba; Achir Yani S. Hamid; Novy H.C. Daulima (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the benefits of emotional support and spiritual coping against psychological distress in caregivers of people with schizophrenia. The method used is a systematic review through an adjusted article search for the formulation of research questions with the PICO formula in the EBSCOhost, ProQuest, SpringerLink, ScienceDirect, and Clinicalkey for Nursing databases. The results showed that emotional support and spiritual coping can improve coping skills thereby reducing psychological distress and minimizing the effects of loss of self to depression. In conclusion, emotional support and spiritual coping have benefits as adaptive coping to psychological distress in caregivers of people with schizophrenia. Keywords: Emotional Support, Psychological Disorders, Spiritual Coping